Diel gene expression profiles of a phosphorus limited mountain lake using metatranscriptomics. (26th November 2012) - Vila‐Costa, Maria; Sharma, Shalabh; Moran, Mary Ann; Casamayor, Emilio O.
Summary: The genetic basis of bacterial functionality in freshwater systems remains largely unexplored despite its relevance in biogeochemical cycles. In this study, we used metatranscriptomic sequencing to analyse day and night gene expression profiles of the bacterial planktonic assemblage from the phosphorus (P) limited Lake Llebreta (1620 m above sea level) in the Limnological Observatory of the Pyrenees (LOOP, Central Pyrenees). The goal of the study was to obtain clues about the ecological strategies of bacteria in a highly oligotrophic environment, particularly those related to processing P and energy capture. An average of 37 871 unique reads were obtained per treatment using 454 pyrosequencing of amplified messenger RNA (mRNA), of which ∼ 37% matched a protein function in BLASTx analysis against the NCBI RefSeq database. In general, an overabundance of transcripts for energy acquisition (e.g. photosynthesis, oxidative phosphorylation, proteorhodopsins and bacteriochlorophyll a ) was observed in the day compared with the night. Several different forms of P were metabolized by the community, with the relative abundance of transcripts related to phosphonate and phosphate uptake pointing to a major role of organic P in controlling this ecosystem. Bacteroidetes and Betaproteobacteria were the most actively transcribing phyla in the community, but showed different strategies for supplemental sources of energy: Bacteroidetes appeared to rely on creating H+ gradients across the membrane by using proteorhodopsins during the day and pyrophosphatases at night, whereas Betaproteobacteria appeared to be oxidizing carbon monoxide (CO) that potentially was generated by photooxidation of dissolved organic matter. When these diel freshwater metatranscriptomes were compared with those from two pelagic marine systems, gene expression patterns distinguished freshwater versus marine samples but showed common differences between day and night transcriptomes related to energy production.